Analysing brand strength – corporate financial performance link for companies listed on the Warsaw Stock Exchange - Urbanek, Grzegorz (Analiza związków pomiędzy siłą marki a wynikami finansowymi przedsiębiorstw notowanych na Giełdzie Papierów Wartościowych w Warszawie, 2017)
The opinion that a strong brand is a valuable resource for a company which may significantly influence company performance and contribute to shareholder value creation is gaining wider acceptance. However, empirical studies which confirm this view are relatively few. The purpose of this article is to examine the link between brand strength and corporate financial performance, including shareholder value creation. A number of performance indicators were used in this study – profitability ratios (ROA, ROE, ROIC) and the shareholder value creation proxy indicator – P/BV. The empirical data regarding brand strength were drawn from the annual ranking of the strength of Polish brands, while the financial data of companies were taken from a panel consisting of 56 companies listed on the Warsaw Stock Exchange, observed over a seven-year period from 2008 to 2014. Numerous regression models were examined in order to test hypotheses on links between brand strength and various financial performance indicators. The obtained results support most of the hypotheses, concluding that there is a statistically significant relationship between brand strength and company performance, although the strength of these relationships differs depending on the type of performance indicator. This study contributes to the development of corporate finance literature as well as value based marketing concepts. Apart from its academic aspects, this paper contributes to business practice development since it demonstrates the legitimacy of marketing investments in brand development
Ekonometria = Econometrics, 2017, Nr 2 (56), s. 92-103
Keywords: brand strength; brand equity; financial performance; shareholders value; profitability ratios; siła marki; kapitał marki; wyniki finansowe; wartość dla akcjonariuszy; wskaźniki rentowności